Conflito e cooperação entre relações mediadas pelo computador - Alex Primo (Contemporanea : Revista de Comunicação e Cultura, 2005)
Blogs and Orkut have updated the interest for the study of interactions in virtual communities. But are they just the stage for mutual support and pure consensual cooperative relations? This paper aims to investigate which is the role of conflict in computer mediated interactions, understanding that it is not a radical opposite to cooperation. With this focus, after a dicussion on the sociological impact of conflict, a critical analyses of the following issues is presented: computer simulations of the prisioner's dilemma, Groupthink, the Tragedy of the Commons, production and circulation of public goods in cyberspace and the structural conditionings of certain digital communication services.